Estudo das propriedades termo-ópticas de vidros teluritos co-dopados com Tb3+ e Yb3+ - LIMA, Guilherme de Sousa; GOMES, Leonardo Moreira e Silva; Capiotto, Adriana do Carmo; LIMA, Sandro Marcio (ANAIS DO ENIC, 2026)
.